Basic financing principles of anti-covid measures: the case of the bank for international settlements - Leonid Taraniuk; Irina D'yakonova; Karina Taraniuk; Hongzhou Qiu (Health Economics and Management Review)
The study's main purpose is to study the process of financing anti-COVID measures by the Bank for International Settlements (BIS) during the pandemic COVID-19. Systematization of literature sources and approaches to solving the problem of low level of financial assistance in combating COVID-19, especially for developing economies, showed a need to identify positive and negative factors affecting the BIS during the COVID-19 pandemic. The relevance of solving this scientific problem is a need for priority funding health care to prevent the spread of viral infection COVID-19. The study of anti-COVID measures by BIS during the global pandemic was carried out in the following logical sequence: determining the relevance of the topic; analyzing the scientific background on the research topic; establishing the research methodological basis; providing conclusions and recommendations. Methodological tools of this study are as follows: comparative analysis, scientific abstraction, systematic approach, and generalization method. This study covers the 2019-2020 years. The object of the study was a financial company – the BIS, which can effectively finance anti-COVID measures during the pandemic COVID-19. The article presents an empirical analysis of the possibility to finance anti-COVID measures by the BIS during the pandemic. The findings showed an urgent need to find additional funding sources to finance anti-COVID measures. The study empirically confirms and theoretically proves that the BIS's positive and negative factors are crucial in providing effective anti-COVID measures. The authors determined negative and positive factors influencing the BIS work during the pandemic. Findings allow to find factors for solving management problems regarding the financing of anti-COVIV measures. Besides, they contribute to forming directions to optimize the collaboration between countries' financial institutions and the BIS. The study results could be useful for effective management decisions by managing the BIS in financing anti-COVID measures.